The role and regulation of the urokinase receptor in asthma and COPD - Portelli, Michael A. (2013)
The urokinase plasminogen activator receptor (PLAUR) is a membrane anchored receptor that has been associated with a number of disease states. In these diseases, elevated receptor levels were associated with increased disease aggressiveness and higher mortality rates. Through genetic studies PLAUR has been identified as an asthma susceptibility gene. In these studies, coding and untranslated region single nucleotide polymorphisms showed association with asthma diagnosis and decline in lung function. In addition, association with baseline lung function in smokers and PLAUR SNPs was identified. This suggests that PLAUR plays a role in respiratory disease.